MU`JAM `ARABĪ DAN URGENSINYA DALAM PEMBELAJARAN BAHASA ARAB DI PERGURUAN TINGGI AGAMA ISLAM - Suhaimi Suhaimi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
Among the latest problems encountered in the Arabic teaching in Islamic University is the poor ability of students in comprehending Arabic texts, either classic or contemporary ones. This is not only caused by the insufficiency of student ability in understanding sentence structure, but also the scantiness vocabulary mastery. The use of mu’jam ‘arabi as one of the language learning methods is very important. Unfortunately in Islamic university, there is no exclusive Arabic encyclopedia. This paper explores the urgency of mu’jam in coping with some problems of Arabic teaching in Islamic university, such as IAIN, STAIN and others.